Upper Cambrian carbonate sequences of the Argentine Precordillera and the Steptoean C-Isotope positive excursion (SPICE) - Sial, A. N. (2008)
Carbon and Sr-isotope profiles in Upper Cambrian platformal carbonate Formations in the Precordillera, western Argentina (Zonda, La Flecha and La Silla Formations), were constructed for three representative sections: (a) Quebrada de la Flecha, Eastern Precordillera, (b) Cerro La Silla, Central Precordillera and (c) Quebrada de La Angostura, northern part of the Central Precordillera. At Quebrada de La Angostura, upper part of the La Flecha Formation, δ13Ccarb varies continuously up-section from - 2.0 to + 5.6‰ (PDB) and records the SPICE anomaly (+ 5‰) reported for the first time in South America. The peak of this excursion is characterized by intercalated 2 m thick beds of black shale with marl and limestone that record the onset of a sea-level change. The Steptoean Zonda Formation dolomites at the Quebrada de la Flecha exhibit a total δ13C range from - 2.7 to + 0.6‰ with discrete positive anomaly about 200 m from the transition to the overlying Sunwaptan La Flecha Formation. Pronounced C-isotope anomaly (- 5.6‰) is observed in the La Flecha Formation at about 300 m below the transition to the La Silla Formation. At the Cerro La Silla section, the Zonda Formation exhibit δ13C values of ∼ - 1‰, increasing slightly at the transition to the La Flecha Formation (- 1 to 0‰). The transition of the La Flecha to the La Silla Formations is characterized by alternation of black shales and dolomitic limestone with a discrete positive C-isotope excursion, probably corresponding to the SPICE. At the Quebrada de La Flecha, 87Sr/86Sr for the Zonda Formation varies from 0.70924 to 0.70955 and for the La Flecha Formation from 0.70908 to 0.70942. At Cerro La Silla this ratio varies from 0.70914 to 0.70923 for the La Flecha Formation, and from 0.70898 to 0.70980 for the La Silla Formation. At the Quebrada de La Angostura, ratios for the La Flecha carbonates range from 0.70918 to 0.70993. The overall variation of 87Sr/86Sr is consistent with globally reported Upper Cambrian seawater values at ca. 500 Ma. The unambiguous record of SPICE in the La Flecha Formation at the Quebrada de La Angostura supports a Steptoean age for its deposition and allows precise local, regional, and global stratigraphic correlation. The pronounced negative C-isotope excursion recorded in the La Flecha Formation carbonates at the Quebrada de La Flecha is likely equivalent to that registered in Sunwaptan carbonates of North America and Australia, and might be tied to a global event, as a valuable tool in stratigraphic correlation (SNICE, acronym for Sunwaptan negative isotope carbon excursion).